KESADARAN DAN IMPLIKASINYA BAGI KEHIDUPAN MANUSIA: Studi Māṇḍūkya Upaniṣad - Suprapti, Ketut; Girinata, I Made; Brahman, I Made Adi (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The study of consciousness has been a central focus in various philosophical and spiritual traditions throughout the world. One ancient text that investigates this concept in depth is the Māṇḍūkya Upaniṣad, an ancient Hindu text that focuses on the notion of consciousness in the context of human existence. This abstract explores the implications of the understanding of consciousness as revealed in the Māṇḍūkya Upaniṣad for human life. In this article, key concepts such as Turiya, atman, and the network of relationships between consciousness and reality will be discussed. Additionally, the practical implications of this understanding for everyday life are also debated. Through a textual and philosophical analysis approach, this abstract aims to expand understanding of consciousness and how this understanding can bring significant changes in human life. In conclusion, this study highlights the importance of in-depth reflection on consciousness in the context of Hindu spirituality and philosophy, as well as its relevance to human life today.